Oxygen limitation is not the cause of death during lethal heat exposure in an insect. (31st January 2019) - Lehmann, Philipp; Javal, Marion; Terblanche, John S.
Abstract : Oxygen- and capacity-limited thermal tolerance (OCLTT) is a controversial hypothesis claiming to explain variation in, and mechanistically determine, animal thermal limits. The lack of support from Insecta is typically argued to be a consequence of their high-performance respiratory systems. However, no studies have reported internal body oxygen levels during thermal ramping so it is unclear if changes in ambient gas are partially or fully offset by a compensatory respiratory system. Here we provide such an assessment by simultaneously recording haemolymph oxygen (pO2 ) levels—as an approximation of tissue oxygenation—while experimentally manipulating ambient oxygen and subjecting organisms to thermal extremes in a series of thermolimit respirometry experiments using pupae of the butterfly Pieris napi . The main results are that while P. napi undergo large changes in haemolymph pO2 that are positively correlated with experimental oxygen levels, haemolymph pO2 is similar pre- and post-death during thermal assays. OCLTT predicts that reduction in body oxygen level should lead to a reduction in CTmax. Despite finding the former, there was no change in CTmax across a wide range of body oxygen levels. Thus, we argue that oxygen availability is not a functional determinant of the upper thermal limits in pupae of P. napi .